The Effect of Problem-Based Learning Model Assisted by Scratch in Grade VII Informatics Learning on Critical Thinking Skill - Afifudin, Muhammad Abdu; Rusijono, Rusijono; Susarno, Lamijan Hadi; Rokhman, Ayla Yuli (EDUTIC, 2025)
This study aims to determine the effect of the Scratch-assisted Problem-Based Learning (PBL) model on the critical thinking skills of seventh-grade students in Informatics subject, specifically on computational artifact development. The research employed a quantitative approach with a quasi-experimental design, using a pretest-posttest control group. The research sample consisted of two classes: an experimental class that implemented the Scratch-assisted PBL model, and a control class that used a conventional learning model. The critical thinking assessment instrument was developed based on five indicators from Facione: interpretation, analysis, evaluation, inference, and explanation. Data were analyzed using an independent samples t-test to determine the significance of the differences between the groups. The results of the independent samples t-test showed a statistically significant difference between the experimental and control groups (t(38) = 3.45, p = 0.004). The mean posttest score of the experimental group increased significantly from 62.4 to 83.6, with a large effect size (Cohen's d) of 1.24. The research sample consisted of 40 seventh-grade students divided into two groups. The inference and explanation indicators showed the highest improvement. In addition to the score improvement, project-based learning with Scratch also facilitated 21st-century skills such as collaboration, problem-solving, and student digital agency. The integration of Scratch provided space for computational thinking, solution visualization, and self-reflection. This study recommends the use of digital-based PBL models as an innovative learning strategy aligned with the Merdeka Curriculum.